English in Indonesia - Rini, Julia Eka (Beyond Words, 2014)
Abstract Indonesia is a multilingual country with various local languages and language courses on various foreign languages. Among the foreign languages, English and Chinese are the prominent ones. This article aims at portraying the position of English in Indonesia among the languages spoken and used in Indonesia, especially Chinese. The discussion focuses on English in business, education, and pop culture. In the context of Englishes, this article also discusses